Characterization of TiO2: ZnO thin films by sol-gel dip coating method - Aksan, O. A.; Bahşi, Z. Banu (American Institute of Physics Inc., 2021)
The incorporation of ZnO in TiO2 is essential for improving physical and optical properties. In this study, thin films with molar ratios of 1:1 and 1:0.5 TiO2: ZnO were produced on glass substrates using the sol-gel dip coating method. X-ray diffraction (XRD) and scanning electron microscopy (SEM) were used to characterize the microstructure and surface morphology of the films. Prism Coupler (Metricon Model 2010/M) was used to measure the refractive index and thickness of thin films. Image J software was used to calculate the surface porosity of thin films. When the ZnO concentration in TiO2: ZnO thin films was reduced to 0.5, higher porosity and a lower refractive index value were obtained. The results show that the ratio of ZnO had a significant effect on the refractive index values of TiO2: ZnO thin films. All films had an amorphous structure with no cracks. It was determined that the resulting films integrated with a prism coupler can be used as a transducer in an optical waveguide biosensor. © 2021 Elsevier B.V., All rights reserved.
10th International Advances in Applied Physics and Materials Science Congress and Exhibition -- Fethiye, Virtual -- 169880